(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The current research aims to test the correlation and influence relationship between smart leadership with its dimensions represented by (spiritual intelligence, rational intelligence, emotional intelligence) and talent management with its dimensions represented by (attracting talents, retaining talents, developing talents, managing and evaluating talents) in the General Directorate of Education in Nineveh Governorate. And the analytical approach was adopted for the data collected from a sample of (42) leaders, through a questionnaire prepared for this purpose. And the ready-made statistical software (SPSS V.26) was adopted in testing the research hypotheses, and it reached several results, the most important of which is the existence of significant correlations and influence between smart leadership in terms of its dimensions (combined and individual and the enhancement of talent management in the researched organization, and in a manner that presented several necessary proposals for the organizations in general and the researched in particular with regard to the two research variables and the relationship between them.